Perbedaan komitmen karier ditinjau dari data demografi pada anggota kepolisian - Sukma, Norma Nadiya; Ingarianti, Tri Muji (Universitas Muhammadiyah Malang, 2024)
The Indonesian National Police is a state apparatus responsible for maintaining security, public order, and law enforcement, as well as protecting and serving the community in safeguarding the Republic of Indonesia. Career commitment refers to an individual's dedication to their work in pursuit of career goals through active participation. Those who are committed to their careers strive to achieve their objectives. This study aims to examine the differences in career commitment among police officers based on demographic data. Utilizing a quantitative approach with a comparative research design, the study involved 125 police members from one of the police agencies in Pasuruan Regency, East Java. The purposive sampling technique was employed to select participants. The study used the Career Commitment Measure (CCM) as the assessment tool. The findings indicate that there are significant differences in career commitment related to demographic factors such as career development stages, length of service, and educational background.